2002
DOI: 10.1083/jcb.200203035
|View full text |Cite
|
Sign up to set email alerts
|

The roles of Fzy/Cdc20 and Fzr/Cdh1 in regulating the destruction of cyclin B in space and time

Abstract: In Drosophila cells cyclin B is normally degraded in two phases: (a) destruction of the spindle-associated cyclin B initiates at centrosomes and spreads to the spindle equator; and (b) any remaining cytoplasmic cyclin B is degraded slightly later in mitosis. We show that the APC/C regulators Fizzy (Fzy)/Cdc20 and Fzy-related (Fzr)/Cdh1 bind to microtubules in vitro and associate with spindles in vivo. Fzy/Cdc20 is concentrated at kinetochores and centrosomes early in mitosis, whereas Fzr/Cdh1 is concentrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 63 publications
6
145
1
Order By: Relevance
“…Recently, it has been shown that interaction between Mad2 and Cdc20 requires Cdk activity (Chung and Chen, 2003;D'Angiolella et al, 2003). When the spindle checkpoint is activated, the proteolytic destruction of securin (Zur and Brandeis, 2001) and cyclin B (Raff et al, 2002) by APC Cdc20 is inhibited, which leads to cell cycle arrest with unseparated chromatids (Cohen-Fix et al, 1996;Zou et al, 1999b), avoiding the risk of chromosome missegregation and mitotic catastrophe. Spindle checkpointdeficient cells develop numerical chromosome instabilities, as reported for a number of different cancers such as colon, lung, breast and bladder cancer, and leukemia and lymphoma cells, where mutations in the Mad and Bub genes are identified especially in the kinetochore localization domain (Cahill et al, 1998;Masuda and Takahashi, 2002;Ru et al, 2002).…”
Section: Mitotic Checkpoints Involving Apc Regulation and Tumorigenesismentioning
confidence: 99%
“…Recently, it has been shown that interaction between Mad2 and Cdc20 requires Cdk activity (Chung and Chen, 2003;D'Angiolella et al, 2003). When the spindle checkpoint is activated, the proteolytic destruction of securin (Zur and Brandeis, 2001) and cyclin B (Raff et al, 2002) by APC Cdc20 is inhibited, which leads to cell cycle arrest with unseparated chromatids (Cohen-Fix et al, 1996;Zou et al, 1999b), avoiding the risk of chromosome missegregation and mitotic catastrophe. Spindle checkpointdeficient cells develop numerical chromosome instabilities, as reported for a number of different cancers such as colon, lung, breast and bladder cancer, and leukemia and lymphoma cells, where mutations in the Mad and Bub genes are identified especially in the kinetochore localization domain (Cahill et al, 1998;Masuda and Takahashi, 2002;Ru et al, 2002).…”
Section: Mitotic Checkpoints Involving Apc Regulation and Tumorigenesismentioning
confidence: 99%
“…A non-degradable allele of cyclin B obtained by mutating its APC/C binding sites persists on centrosomes throughout mitosis, suggesting cyclin B removal from metaphase centrosomes involves its polyubiquitination and subsequent degradation. 60 APC/C-mediated cyclin B degradation requires Vihar, an E2 ubiquitin-conjugating enzyme that also localizes to centrosomes during metaphase before disappearing as mitosis progresses ( Fig. 2A, bottom panel).…”
Section: Centrosome Function Depends On the Proteasomementioning
confidence: 99%
“…1G), centrosomes are centers for ubiquitination activity, governing the action of the anaphase promoting complex/ cyclosome (APC/C) in causing the degradation of substrates such as cyclin B. [45][46][47] Separate studies indicate that the centrosome may also nucleate cellular degradation and proteasome activation at other phases in the cell cycle as well. 48 In 2001, Piel et al made the intriguing observation that the mother centriole must undergo an excursion to the region of the midbody to allow completion of cytokinesis, suggesting delivery of some final signal to promote excision.…”
Section: Roles Of the Centrosomementioning
confidence: 99%